A general Lewis acidic etching route for preparing MXenes with enhanced electrochemical performance in non-aqueous electrolyte - Li, Youbing; Shao, Hui; Lin, Zifeng; Lu, Jun; Liu, Liyuan; Duployer, Benjamin; Persson, Per O. Å.; Eklund, Per; Hultman, Lars; Li, Mian; Chen, Ke; Zha, Xian-Hu; et al. (Nature materials, 2020)
Two-dimensional carbides and nitrides of transition metals, known as MXenes, are a fast-growing family of materials that have attracted attention as energy storage materials. MXenes are mainly prepared from Al-containing MAX phases (where A = Al) by Al dissolution in F-containing solution; most other MAX phases have not been explored. Here a redox-controlled A-site etching of MAX phases in Lewis acidic melts is proposed and validated by the synthesis of various MXenes from unconventional MAX-phase precursors with A elements Si, Zn and Ga. A negative electrode of Ti 3 C 2 MXene material obtained through this molten salt synthesis method delivers a Li + storage capacity of up to 738 C g −1 (205 mAh g −1 ) with high charge–discharge rate and a pseudocapacitive-like electrochemical signature in 1 M LiPF 6 carbonate-based electrolyte. MXenes prepared via this molten salt synthesis route may prove suitable for use as high-rate negative-electrode materials for electrochemical energy storage applications. Two-dimensional transition metal carbides and nitrides, known as MXenes, are currently considered as energy storage materials. A generic Lewis acidic etching route for preparing high-rate negative-electrode MXenes with enhanced electrochemical performance in non-aqueous electrolyte is now proposed.